A plate of hope : the inspiring story of Chef José Andrés and World Central Kitchen - Frankel, Erin (Random House Studio, 2024)
"A biography about chef José Andrés, who, through his World Central Kitchen organization, is fulfilling a vision to feed people in need all over the world"--